INTERTEXTUALITY IN GLOBAL LITERATURE: A CROSS-CULTURAL PERSPECTIVE - Kipchakova Sanobar (Western European Studies, 2025)
Intertextuality plays a crucial role in global literature, enabling authors to engage in cultural dialogues across time and space. This article explores how literary works incorporate intertextual elements—such as allusions, quotations, and stylistic influences—to establish connections between different cultural traditions. By analyzing key examples from Western and Eastern literary canons, the study highlights how intertextuality fosters mutual understanding and enriches literary interpretation. The article also examines the role of translation in intertextual relationships, demonstrating how linguistic and cultural nuances influence the reception of intertextual references. Ultimately, this research underscores the significance of intertextuality as a tool for cross-cultural exchange and literary evolution
Keywords: Intertextuality; global literature; cultural dialogue